Підвалини військової політики гетьмана Павла Скоропадського - Барановська, Н. М. (Видавництво Львівської політехніки, 2014)
Проаналізовано основні засади військової політики гетьмана Павла Скоропадського, роль і місце національних Збройних Сил у державотворчих процесах квітня – грудня 1918 p. Розглянуто державно-правове підгрунтя формування національної армії та її кадрового забезпечення. The article analyses the main principles of hetman Pavlo Skoropadskyj military policy, role and place of national Military Рowers in state creation processes of April – December, 1918 and considers foundations of national army formation and staffing. Though, recently, in the Ukrainian historical science appeared many scientific works that consider questions of the state formation in period of hetmanate, but the problems of army formation are investigated insufficiently. It is necessary to notice, that despite of complexity of mutual relations in the Ukrainian society and all external threats, during the period of Pavlo Skoropadskyj governing, the questions connected with development of an official military state policy gain an accurate outline. Creation of regular national army as guarantor of state sovereignty is first and foremost. The idea of Central rada about replacement of army by national policy has finally been rejected and realisation of program, concerning formation of the regular, professionally trained Armed forces has begun. The legislative base of military support which not only introduced legal framework for formation of the Ukrainian army and fleet, but also guaranteed their development because of the up-to-date military achievements of that time civilised world, has been developed. Considerable reorganisation of the Ukrainian army’s higher command institutions concerning as structural formation, as operative management has taken place. A set of professional educational institutions has been created for military personnel training. It testifies that P. Skoropadskyj was devoted to an idea of the Ukrainian statehood and was well aware of the role of an combat-ready constant army in question of protection of Ukraine from military aggression of other countries. And with that, P. Skoropadskyj’s protective concept did not provide constant army involvement to police within the country, and officer military formations were used only for suppression of political protest actions and country disorders. However, hetman didn’t managed to push the matter through after all, because of the activity of destructive forces and to create real powerful military force, during his short governing, because even the Serdjutska Guards division that consisted of representatives of substantial farmers and was considered as a support of hetmanate, has come over the side o the Directory.
Keywords: військова політика; гетьман; Павло Скоропадський; армія; military politics; hetman; Pavlo Skoropadskyj; army